Exploring genetic associations of Crohn’s disease and ulcerative colitis with extraintestinal cancers in European and East Asian populations - Yu, Chengdong; Xu, Jiawei; Xu, Siyi; Tang, Lei; Han, Qinyuan; Zeng, Xiaoqiang; Huang, Yanxiao; Yu, Tenghua; Sun, Zhengkui (Frontiers in Immunology, 2024)
Background: Previous studies have reported associations of Crohn’s disease (CD) and ulcerative colitis (UC) with the risks of extraintestinal cancers, but the causality remains unclear. Methods: Using genetic variations robustly associated with CD and UC extracted from genome-wide association studies (GWAS) as instrumental variables. Nine types of extraintestinal cancers of European and Asian populations were selected as outcomes. We used the inverse variance weighted method as the primary approach for two-sample Mendelian randomization analysis. Sensitivity analyses were carried out to evaluate the reliability of our findings. Results: In the European population, we found that CD showed a potential causal relationship with pancreatic cancer (OR: 1.1042; 95% CI: 1.0087-1.2088; P=0.0318). Meanwhile, both CD (outliers excluded: OR: 1.0208; 95% CI: 1.0079-1.0339; P=0.0015) and UC (outliers excluded: OR: 1.0220; 95% CI: 1.0051-1.0393; P=0.0108) were associated with a slight increase in breast cancer risk. Additionally, UC exhibited a potential causal effect on cervical cancer (outliers excluded: OR: 1.1091; 95% CI: 1.0286-1.1960; P=0.0071). In the East Asian population, CD had significant causal effects on pancreatic cancer (OR: 1.1876; 95% CI: 1.0741-1.3132; P=0.0008) and breast cancer (outliers excluded: OR: 0.9452; 95% CI: 0.9096-0.9822; P=0.0040). For UC, it exhibited significant causal associations with gastric cancer (OR: 1.1240; 95% CI: 1.0624-1.1891; P=4.7359×10–5), bile duct cancer (OR: 1.3107; 95% CI: 1.0983-1.5641; P=0.0027), hepatocellular carcinoma (OR: 1.2365; 95% CI: 1.1235-1.3608; P=1.4007×10–5) and cervical cancer (OR: 1.3941; 95% CI: 1.1708-1.6599; P=0.0002), as well as a potential causal effect on lung cancer (outliers excluded: OR: 1.1313; 95% CI: 1.0280-1.2449; P=0.0116). Conclusions: Our study provided evidence that genetically predicted CD may be a risk factor for pancreatic and breast cancers in the European population, and for pancreatic cancer in the East Asian population. Regarding UC, it may be a risk factor for cervical and breast cancers in Europeans, and for gastric, bile duct, hepatocellular, lung, and cervical cancers in East Asians. Therefore, patients with CD and UC need to emphasize screening and prevention of site-specific extraintestinal cancers.